Use of Learning Video Media to Improve Mathematics Learning Results About Space Building - Ni’matul Machmudah (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve mathematics learning result about space building of grade II. The research conducted was Classroom Action Research (PTK) with 3 cycles, the research place was the unit where the researcher taught. The results of the first cycle were 63.63% of students had passed the KKM, in the second cycle students who passed the KKM were 81.82% and in the third cycle 95.4% of the students passed the KKM. With an increase in the number of students who pass the KKM, the use of instructional video media can improve student learning outcomes in mathematics, especially about building space.